Bio-prospection of fungi from a fragment of cerrado in central Brazil for biotechnological applications - Leonardo Da Silva, Lucas; Moreira, Izabel Cristina; Machado E Silva, Thâmara; Batista Da Silva, Larissa; Santos, Thales Antony Assis; De Oliveira, Letícia Mikaelly; De Souza, Denes Ferraz; De Oliveira Brito, Andressa; Dos Santos, Solange Xavier [UNESP] (My University, 2018)
Considering the importance of bio-prospection studies involving species from threatened environments that are of great biological richness and endemism, this work aimed to investigate the biotechnological potential of fungi from different habitats in a fragment of Cerrado. The fungi were isolated in culture, and some were selected for the prospection of enzymes that are of industrial interest, for antimicrobial activity and preliminary toxicity. Carboxymethyl cellulose and peroxidase activity was detected in all isolates evaluated. In the tests for antimicrobial activity, the fungal metabolites did not show growth inhibition for the bacterial strains analyzed, and in the toxicity assays these metabolites were shown to be innocuous for Artemia salina larvae. Although the toxicity evaluation still requires complementary assays, these results justify the continuation of bio-prospection studies on the biotechnological potential of these fungi, showing them to be promising candidates for use in processes applied directly to humans or to the environment.
Bioprospecção de fungos de um fragmento de cerrado no Brasil central para aplicações biotecnológicas
Keywords: Ascomycetes; Basidiomycetes; Lignocellulolytic enzymes; Toxicity